Analisis Metode Pembelajaran di Sekolah Dasar - Ayu Anjani; Gita Harnum Syapitri; Rifka Izatul Lutfia (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2020)
This study aims to determine the learning methods used in elementary schools. The learning method used must be adapted to the learning material and learning media that will be used in the teaching and learning process. With the learning method, it is expected that the teaching and learning process can be carried out well so that it can improve the quality and quantity of students in the future. Effective learning methods can facilitate the implementation of the learning process and facilitate students in absorbing the material conveyed by the instructor.